MODEL PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM MULTIKULTURAL - Sismanto Sismanto (STAI Sangatta Kutai Timur, 2022)
A pluralistic society where people can live side by side peacefully in culture requires a curriculum that can guide teachers, schools, and parents in teaching and learning activities at school and at home. This study analyzes instructions on approaching and modeling the multicultural Islamic education curriculum implemented at a private elementary school in Sangatta. Research using qualitative and the researcher is part of the key instrument. Respondents in this study were principals, vice-principal, and teachers of Islamic education. They are collecting data using observation, interview, and documentation techniques. The results show that: (1) The multicultural-based Islamic religious education curriculum approach used in Sangatta private elementary school contributes an additive contribution. (2) The model for developing the multicultural Islamic Islamic education curriculum at private elementary school Sangatta uses administrative and grass-root models.